The Total Reward of Physicians - Buchelt, Beata; Beck-Krala, Ewa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The aim of this paper is to identify and evaluate currently used methods of remunerating doctors in hospitals then to lay out general recommendations for rewarding these medical professionals in Polish health care. Research Design & Methods: A critical analysis of the literature review was done. The selection of literature was dictated by the specificity of the research problem and the multiplicity of perspectives and concepts of management that were analysed. Findings: The literature review shows that the remuneration solutions for doctors do not capture a holistic view of the effectiveness of doctors’ work, nor do they consider the specificity of this profession. The term Pay for Performance used in the literature in the context of remunerating doctors is defined too narrowly. That applies to remuneration for the number of procedures performed and for hours worked. This approach to remuneration comes in for widescale criticism in the literature as it is not conducive to the high quality of medical services provided. According to the research, physicians are also rewarded for qualifications or for actions consistent with the values of medical entities. Implications / Recommendations: The holistic approach to the effectiveness of doctors’ work and the characteristics of the medical profession determine the implementation of solutions based on a Total Rewards programme. The structure of the rewards package for physicians should stimulate pro-effective behaviour among physicians – that is, they develop specialist and non-specialist competencies and perform a defined number of medical procedures. Such an approach implies the use of both tangible and intangible factors that help bring about desired behaviours among these personnel. Contribution: The paper reports on the development of guidelines for total rewards of doctors, referring to both the key features of their profession and the specificity of their work.